P–066 Does microfluidic sperm sorting (MSS) affect embryo euploidy rates in couples with high sperm DNA fragmentation (SDF)?. (6th August 2021) - Keskin, M; Pabuçcu, E G; Tufan, A; Demirkıran, D.Ö; Pabuçcu, R
Abstract: Study question: Does MSS (microfluid chip-sorted spermatozoa selection) provide improvement on embryo quality and euploidy rates in couples with high SDF (sperm DNA fragmentation) and previous failed in vitro fertilization/ intracystoplasmic sperm injection (IVF/ICSI) cycles? Summary answer: Use of MSS technique provides higher number of top quality blastocysts compared to density gradient centrifugation (DGC), however euploidy and live birth rates weren't improved. What is known already: Previously it has been reported that sperm DNA damage leads to poor embryo development and there is a significant association between SDF and high embryo aneuploidy rates. Recently this fact raised attention to sperm selection techniques such as MSS to enhance embryo quality, miscarriage rates and embryonic euploidy rates. Study design, size, duration: This was a retrospective electronic medical record (EMR) analysis of a tertiary assisted reproduction center between 2016 and 2020. All EMR were reviewed to select eligible cases as; couples undergoing a new IVF/ICSI cycle with PGT-A (preimplantation genetic testing for aneuploidies). In total, data from 243 patients were obtained for the analysis that accounts for 688 embryos. Participants/materials, setting, methods: Patients had at least 2 previous failed IVF cycles and males had at least 20% SDF. In their new cycles, MSS was offered, preceding ICSI and PGT-A. Couples who accepted the technique were assigned to MSS group (92 cycles with 310 embryos) and the rest were managed with DGC and assigned as controls (151 cycles with 378 embryos). Azoospermia cases and women with age>43, uterine abnormalities, trombophilia were excluded. Biopsies were performed at blastocyst stage. Main results and the role of chance: Two groups were comparable in terms of demographic data including women and men age, SDF, sperm parameters and cycle characteristics. There was no difference between groups in terms of fertilization rates (MSS 85% vs DGC 79% p = 0.9), euploidy rates (MSS 53.2% vs DGC 50.7% p = 0.3), mean no of euploid embryo per patient (MSS 1.09 vs DGC 0.95 p = 0.3), positive pregnancy test (MSS 50% vs DGC 38.4% p = 0.06), clinical miscarriage (MSS 7.6% vs DGC 6.6% p = 0.7) and live birth rates (LBR)(MSS 42.4% vs DGC 31.7% p = 0.09). Total no of blastocysts and top quality blastocysts were significantly higher in MSS group than in DGC (3.9 vs 2.5 p < 0.01 and 1.6 vs 0.8 p < 0.001 respectively). Limitations, reasons for caution: Retrospective design, small sample size, lack of proper randomization and power analysis are the main limitations. Wider implications of the findings: Offering PGT-A to couples with unexplained repeated IVF failures and high SDF seems feasible. MSS for such cases improves embryonic division process as improved blastulation rates were documented. However, euploidy rates were not improved in MSS group revealing that other factors influence comprehensive chromosomal status of an embryo. Trial registration number: Not applicable